PENGELOLAAN ARSIP INAKTIF KEUANGAN DI BADAN PEMERIKSA KEUANGAN PERWAKILAN PROVINSI D.I. YOGYAKARTA - , DOMINICUS SATRIA Y ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report carrying a theme entitled Archival Processing of Inactive Finance on the Badan Pemeriksa Keuangan in Special Provence Yogyakarta. This final report is made after finishing the Job Practice. Final project report writing aims to find out the processing operation system on the inactive records are maintained on the Badan Pemeriksa Keuangan in Special Provence Yogyakarta. Financial archives handling in the Supreme Audit Board itself consists of several stages, started from sorting the archive, an archive identification, the handling of the archive, so that the archive can be used up to the users and can be run effectively and efficiently in the appointment back. Data collection methods used in the preparation of this final report is the observation. Observing and doing activities directly in Badan Pemeriksa Keuangan in addition to conducting interviews with official directly involved in the management of dynamic financial archive at Supreme Audit Board, and literature references by using materials to obtain the data and information in report writing. The main conclusion of the overall arrangement of the Badan Pemeriksa Keuangan archives on Yogyakarta is already quite good, but still not running optimally on the processing, due to the limited human resources expert in the scope of archiving.